Middle–Late Triassic sedimentary provenance of the southern Junggar Basin and its link with the post-orogenic tectonic evolution of Central Asia - Jialin Wang; Chaodong Wu; Yue Jiao; Bo Yuan (Scientific Reports, 2021)
Abstract Due to the unknown Triassic volcanism in the Junggar Basin, the Middle–Late Triassic sedimentary provenance in the southern Junggar Basin (SJB) has long been controversial. Detrital zircon grains from 13 samples of the Middle–Upper Triassic Xiaoquangou Group in the SJB were analyzed using zircon U–Pb geochronology to constrain the provenance of Triassic sedimentary rocks and to further understand their source-to-sink system. Comparison of detrital zircon U–Pb age distributions for 13 samples reveals that the Triassic age populations predominate in sediments of the northern Bogda Mountains, with subordinate in the southern Bogda Mountains, and no or minimal in the North Tianshan (NTS). Coupled with sandstone petrological, sedimentary geochemical and paleocurrent data, the Triassic detrital zircon grains of the Xiaoquangou Group in the SJB were probably input from the Bogda Mountains. As Pennsylvanian and Mississippian zircon grains are mainly derived from the NTS and Central Tianshan (CTS), the provenance of the Xiaoquangou Group includes the NTS, CTS and Bogda Mountains. But the different samples in different sink areas have different provenances, originating from at least four source-to-sink systems. The supply of sediments from the Bogda Mountains started in the Late Triassic, suggesting initial uplift of the Bogda Mountains.